THE RELATIONSHIP OF KNOWLEDGE AND THE ROLE OF PARENTS IN STIMULATING THE DEVELOPMENT OF CHILDREN AGED 3–24 MONTHS - Nuryanah, Yayah; Putri, Dian Priharja (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Background: Every child experiences very important stages of growth and development in the First Thousand Days of Life (1000 HPK) of birth. Stimulation of growth and development can be carried out by parents, caregivers, educators and health workers. Lack of stimulation can cause permanent developmental disorders.From In Indonesia in 2020, there were 13-18% of toddlers experiencing various child development problems such as motor delays, language, behavior, autism and hyperactivity. The process of growth and development in children occurs very naturally. To realize children's development according to their age, parents must have knowledge about children's growth and development and play a role in stimulating children. Research purposes: This research was conducted to determine the relationship between knowledge and the role of parents in stimulating the development of children aged 3–24 months in the working area of Sukaindah Community Health Center, Bekasi Regency in 2023. Research methods: This research is a quantitative research approachcross sectional. The total sample was 102 parents who had children aged 3–24 months who were taken using this techniquepurposive sampling. The knowledge and role of the elderly is measured using a questionnaire, while the child's development is measured usingDevelopmental Pre-Screening Questionnaire (KPSP). Statistical test usingChi-Square. Research result: There is a relationship of knowledge (p= 0.002) and the role of parents (p = 0.002) in stimulating the development of children in the working area of Sukaindah Community Health Center, Bekasi Regency in 2023. Conclusions and recommendations: There is a need for education and outreach to parents to increase knowledge and the importance of the role of parents in stimulating children's development according to their age until they reach optimal levels.